Epidemiology of ovine paratuberculosis in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, New Zealand - Gautam, Milan (Massey University, 2019)
The overall goal of this PhD project was to better understand the general epidemiology of ovine paratuberculosis (PTb) and the speciﬁc molecular characteristics of the causing organism Mycobacterium avium subspecies paratuberculosis in New Zealand. To begin with, current control measures for clinical PTb in New Zealand’s major pastoral livestock species (dairy cattle, beef cattle, sheep, deer) were reviewed. Infection with Map is common in all these species and control is voluntary for all livestock industries. Control measures aim to reduce the incidence rate of clinical PTb rather than to eradicate Map infection. Dairy and deer industries have developed resources describing best-practice management options that assist farmers and veterinarians to advise their clients about speciﬁc control plans. There is no national control programme for sheep and beef cattle. However, unlike for cattle and deer, the use of a commercial vaccine is licensed for sheep. Evidence in this thesis suggests that vaccination may be a cost effective option for ﬂocks that experience a high incidence of clinical disease. For deer, there is a national abattoir surveillance programme that aims to alert farmers of unusually high rates of PTb-like lesions in deer at slaughter. Evaluations of the biological and economic effectiveness of voluntary control still remains to be undertaken for all industries. Work in this thesis estimated the on-farm economic cost of clinical PTb in sheep (ovine Johne’s disease, OJD) in New Zealand. It was based on data about the incidence of clinical PTb and overall mortality from 20 OJD-affected farms. The beneﬁt-cost ratio of vaccination was estimated. Farms were categorized as either ﬁne-wool breed (Merino, Half-bred, Corriedale) or other breeds and calculations were stratiﬁed for these two farm categories. The estimated mortality due to OJD was 2.7 times as high in ﬁne-wool as in other breeds with large variation between farms. A stochastic simulation for a hypothetical ﬂock with 2,000 breeding ewes resulted in an average annual cost of OJD-mortality of NZ $13,100 in ﬁne-wool and NZ $4,300 in other breeds. Vaccinating replacement lambs against OJD would be cost-effective in most ﬂocks when the pre-vaccination annual OJD ewe mortality was >1%. Accurate on-farm observation of OJD to establish incidence would help farmers to make better decisions about vaccination. Frozen-stored faecal and serum samples of individual sheep with no signs of clinical disease from 45 commercial ﬂocks from a 2013 study that determined pooled faecal culture (PFC) status were used to determine faecal Map shedding and antibody in serum. A total of 878 faecal samples were tested with direct faecal real-time quantitative PCR (qPCR) to determine Map shedding prevalence and abundance in individual animals. In addition, the qPCR results were compared with Map antibody ELISA results from 837 corresponding sera to correlate the observed shedding prevalence with sero-prevalence. Overall, 13.1% of faecal samples and 5.8% of serum samples tested positive. The median intra-ﬂock prevalence (IFP) of Map shedding in the qPCR positive ﬂocks was 13.5% with a range of 5–95%. The median IFP of Map ELISA antibody positive ﬂocks was 10% with a range of 5–20%. ELISA results and the DNA concentration in qPCR positive samples were positively correlated. Nevertheless, ELISA was a poor predictor of individual shedding. A more robust assessment of the shedding status of ﬂocks can be achieved by using a combination of qPCR and ELISA of individual animals rather than a single PFC of 20 randomly selected sheep per ﬂock, as was used in the 2013 survey. Type S1 Map isolates from New Zealand and the Australian Telford strain were char- acterized based on single nucleotide variant (SNV) analysis of whole genome sequence data (WGS). A Type S1 genome was completely sequenced and closed for using as a reference for the SNV analysis. Besides deﬁning the genetic relationship between Map isolates from New Zealand, Australia and Europe several phenotypic variables used as surrogates for the severity of PTb in individual hosts were investigated. The New Zealand and Australian isolates formed a closely related group. They were distinctly different from the Type S isolates from countries in Europe. Within New Zealand, Map genotypes and region of sheep farm locations were signiﬁcantly associated (p <0.05). There were no signiﬁcant associations between genotype and surrogates for severity, observed in the animals which the genotypes were isolated from, such as histopathological scores of intestinal lesions, host serology or the gross-pathological diagnosis by veterinarians at necropsy. These results suggested that the phenotypic variation of PTb may depend on factors other than Map-genotype in Type S strain. Further studies are required to sub-stantiate a hypothesis about varying virulence factors of the Map genome in New Zealand sheep. In summary, PTb control in New Zealand is voluntary in all major ruminant livestock industries including sheep. In clinically affected commercial sheep farms, estimated mortality due to OJD was 2.7 times as high in ﬁne-wool as in other breeds, but large variations were observed between farms. PTb vaccination in commercial sheep ﬂocks may be cost effective if annual incidence of OJD attributable ewe mortality is >1%. In non-clinical commercial ﬂocks, the median IFP of Map shedding and Map ELISA antibody positive prevalence was 13.5% and 10% respectively. Approximately 1% ewes in qPCR positive ﬂocks were supershedders. Based on analysis of WGS data, Type S Map genotypes from New Zealand sheep were similar across the country and not affected by the type of breed or disease outcome in hosts.
Keywords: Paratuberculosis; New Zealand; Epidemiology; Mycobacterium avium paratuberculosis; Sheep; Diseases; 300905 Veterinary epidemiology